Approaches to web application performance testing and real-time visualization of results - Ushakova, Iryna; Plokha, Olena; Skorin, Yuri; Ушакова, Ірина Олексіївна; Плоха, Олена Борисівна; Скорін, Юрій Іванович (Харківський національний автомобільно-дорожній університет, 2022)
Problem. Today, performance testing is an integral part of the web applications quality assur-ance whose performance failures and performance issues affect the business of their owners. Goal. The goal of the work is to generalize approaches and methods to improve the quality of web applications and develop recommendations for improving performance testing using open source tools. The object of research is the processes of testing web applications. The subject of research is the approaches, methods and tools of performance testing. Methodology. The study identified the impact of software performance testing on its quality and its main types, namely load testing, stress testing, volume testing, stability testing. The main stages of performance test-ing and their content were identified. To implement modern automated testing technologies, the advantages and disadvantages of the most popular tools for testing performance in the modern IT market and continuous visualization of their results were analyzed and identified. The follow-ing factors should be considered when selecting a performance testing tool: compatibility, scalability, clarity, and monitoring. Time series databases and visualization tools are used for continuous monitoring of test results together with testing tools. Results. During the practical implementation of the research results, the goals of different types of performance testing, indi-cators of normal operation of the system without exceeding the permissible limits, test scenarios and test results were identified. Visualization of test results in JMeter is shown and a board for continuous real-time visualization is created. Originality. The originality of the study lies in un-locking the potential of open source tools for testing the performance of web applications and visualizing its results. On the basis of comparative analysis the spheres of application of tools for performance testing are substantiated. Practical value. The practical value lies in the devel-opment of methodological bases for testing the performance of web applications in real time on the example of the connection of tools Jmeter ¬– InfluxDB – Grafana.
Підходи до тестування продуктивності вебзастосунків і візуалізації результатів у реальному часі
Keywords: testing; web application; performance; load; software quality; quality metrics; тестування; вебзастосунок; продуктивність; навантаження; якість програмного забезпечення; метрики якості; 004.054; 10.30977/BUL.2219-5548.2022.96.0.71